2007
DOI: 10.1182/blood.v110.11.5150.5150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Powered Intraosseous Device for Bone Marrow Sampling.

Abstract: The importance of bone marrow examination in the evaluation of leukemia, multiple myeloma, anemia, pancytopenia, and other disorders is well established. The objective for this study was to evaluate the ability of a powered bone marrow aspiration device to penetrate the intraosseous medullary space of the iliac crest, and to aspirate bone marrow samples for the ultimate purpose of diagnosing disease and monitoring the course of disease and medical therapy. The device was used to obtain bone marrow samples in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…In this study we investigated the facility of obtaining BM core biopsies from small dogs using a 15ga needle from the EZ‐IO Intraosseous Infusion System. We chose this system because (1) a biopsy obtained using a 15ga needle would likely be the smallest core BM biopsy that might yield a diagnostic specimen; (2) the trochar tip of the stylet might facilitate penetration of the cortex better than the bevel tip of a Jamshidi needle; (3) a power driver might facilitate needle advancement; and (4) use of a similar system (OnControl) resulted in improved success of BM aspiration in people . The EZ‐IO system was chosen over the OnControl system because only the former was available; its needles are designed for intraosseous fluid administration and not BM core biopsy and, therefore, have no capture mechanism, such as the tapered end of a Jamshidi needle or split stylet of a Conrad‐Crosby needle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we investigated the facility of obtaining BM core biopsies from small dogs using a 15ga needle from the EZ‐IO Intraosseous Infusion System. We chose this system because (1) a biopsy obtained using a 15ga needle would likely be the smallest core BM biopsy that might yield a diagnostic specimen; (2) the trochar tip of the stylet might facilitate penetration of the cortex better than the bevel tip of a Jamshidi needle; (3) a power driver might facilitate needle advancement; and (4) use of a similar system (OnControl) resulted in improved success of BM aspiration in people . The EZ‐IO system was chosen over the OnControl system because only the former was available; its needles are designed for intraosseous fluid administration and not BM core biopsy and, therefore, have no capture mechanism, such as the tapered end of a Jamshidi needle or split stylet of a Conrad‐Crosby needle.…”
Section: Discussionmentioning
confidence: 99%
“…The system also includes 15ga × 25–90 mm needles for BM aspiration. This system has been reported to be easy and rapid compared with conventional techniques and to result in less pain for patients . Other power drivers are available for rapid placement of needles for intraosseous fluid therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It is also an essential component of the staging process for patients newly diagnosed with lymphoproliferative diseases and certain non-hematopoietic malignancies. Bone marrow examination is instrumental in determining the extent of marrow damage among patients exposed to radiation, drugs, chemicals, and other myelotoxic agents [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The device utilizes a battery-powered drill to insert the bone marrow needle into the iliac bone of adult patients with minimal operator exertion. An evaluation of the first generation device by Cohen and Gore indicated that the device was safe, as well as faster and easier to use than the traditional manual procedure [ 3 ]. The current generation of the device was also assessed in a non-controlled evaluation with similar results [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were not consistent with past research with regard to significantly larger sample sizes. [ 6 8 13 14 ] In addition, some past studies found the manual technique to produce on an average more evaluable marrow specimens;[ 14 ] however, this study found the two techniques to be very comparable. Comparable samples are in line with one other researcher's findings, which also identified crush artifact in the motorized device specimens.…”
Section: Discussionmentioning
confidence: 70%